Localized Amyloidosis of the Nasal Mucosa: A Case Report and Review of the Literature - Takakura, Hiromasa; Tachino, Hirohiko; Takii, Kouji; Imura, Johji; Shojaku, Hideo (Frontiers in Surgery, 2021)
Amyloidosis is a disorder of protein folding in which various proteins automatically aggregate into a highly abnormal fibrillar conformation. Amyloidosis is classified into systemic and localized forms depending on whether the abnormal proteins deposited in several different organs or only a single organ. In localized amyloidosis of the head and neck regions, laryngeal amyloidosis is common; however, localized amyloidosis of the nose is extremely rare. We herein report a case of localized amyloidosis of the nose and review the relevant literature on localized sinonasal amyloidosis. A 41-year-old man presented with a history of severe nasal obstruction, which had persisted for two decades. Nasal endoscopy and imaging studies showed extensive thickening of the bilateral nasal mucosa and diffuse submucosal deposition of calcification. After histopathological and systemic examinations, he was diagnosed with localized amyloidosis of the nasal mucosa. Septoplasty and bilateral inferior turbinoplasty, which consisted of mucosal resection using an ultrasonic bone curette, was performed and his symptoms markedly improved. Localized sinonasal amyloidosis has a good prognosis and surgical resection should be selected as a first-line treatment; however, clinicians should recognize the high probability of recurrence.